2017
DOI: 10.1039/c7ra00788d
|View full text |Cite
|
Sign up to set email alerts
|

Pyridazinediones deliver potent, stable, targeted and efficacious antibody–drug conjugates (ADCs) with a controlled loading of 4 drugs per antibody

Abstract: Delivering potent, stable, targeted and in vivo efficacious antibody–drug conjugates (ADCs) using pyridazinedione functional disulfide re-bridging reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 46 publications
1
77
1
Order By: Relevance
“…All five synthesised PDs 2-6 were incubated with human serum albumin (HSA), the blood's most abundant thiol, at pH 7.4 for 4 h, to determine if there was any reactivity with the protein's accessible cysteine residue. Gratifyingly, no reaction was observed between HSA and all of the trialled PDs, corroborating previously reported results that alkyl thio-PDs are stable in blood-mimicking conditions 29 and unveiling aryl thio-PDs to also be stable in the time-frame of the experiment. As a positive control, maleimide was incubated with HSA alongside PDs 2-6 under identical conditions.…”
supporting
confidence: 90%
“…All five synthesised PDs 2-6 were incubated with human serum albumin (HSA), the blood's most abundant thiol, at pH 7.4 for 4 h, to determine if there was any reactivity with the protein's accessible cysteine residue. Gratifyingly, no reaction was observed between HSA and all of the trialled PDs, corroborating previously reported results that alkyl thio-PDs are stable in blood-mimicking conditions 29 and unveiling aryl thio-PDs to also be stable in the time-frame of the experiment. As a positive control, maleimide was incubated with HSA alongside PDs 2-6 under identical conditions.…”
supporting
confidence: 90%
“…A similar class of molecules called bromopyridazinediones exploit the same principles as substituted maleimides, but pose a hydrolytically stable alternative for cysteine functionalisation [34]. Furthermore, the conjugated pyridazinedione scaffold is stable in vivo (blood) with no further hydrolysis required (Scheme 3b) [35,36]. It is noted however, that this moiety is less reactive towards cysteine than the maleimide scaffold, and so quantitative formation of the bioconjugate can take longer (up to 16 h).…”
Section: Alternative Solutions To Retro-michael Deconjugationmentioning
confidence: 99%
“…[20][21][22] Highly homogenous ADCs with a DAR of two or four have been obtained via this strategy, and these show no decrease in antigen-binding and no decrease in circulation half-life. [23][24][25] However, it has been observed that these disulfide residues can re-bridge in a non-native fashion, resulting in the "half-antibody" species 7, thus yielding a mixture of two antibody conjugates ( Figure 1c). 26,27a,27b Currently there have been no studies to suggest this "half-antibody" species (7) negatively affects the profile of the antibody.…”
Section: Introductionmentioning
confidence: 99%